2020
DOI: 10.3389/fmicb.2020.01867
|View full text |Cite
|
Sign up to set email alerts
|

Availability of Nitrite and Nitrate as Electron Acceptors Modulates Anaerobic Toluene-Degrading Communities in Aquifer Sediments

Abstract: Microorganisms are essential in the degradation of environmental pollutants. Aromatic hydrocarbons, e.g., benzene, toluene, ethylbenzene, and xylene (BTEX), are common aquifer contaminants, whose degradation in situ is often limited by the availability of electron acceptors. It is clear that different electron acceptors such as nitrate, iron, or sulfate support the activity of distinct degraders. However, this has not been demonstrated for the availability of nitrate vs. nitrite, both of which can be respired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 49 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…Metagenomic analysis showed that Proteobacteria, Firmicutes, Actinobacteria and Bacteroidetes were the predominant phyla present in all the microcosms at day 300. The shared genera between manure-treated and control microcosm included Pseudomonas, Delftia, Methylobacterium, Dietzia, Bacillus, Propionibacterium, Bradyrhizobium, Streptomyces, Achromobacter, Microbacterium and Sphingomonas, some of which has been previously reported in oil-contaminated soils [41,43,45], with several members known for their ability to degrade aliphatic and aromatic hydrocarbons [51,52,53]. Whereas Pseudomonas and Sphingomonas have been previously associated with degradation of LMW PAHs [54,55], fermentative, CO 2 -assimilating and methanogenic microorganisms (Bacillus, Methylobacterium and Achromobacter) are known to be key players in HMW PAH degradation [55].…”
Section: Shift In Microbial Community With Manure Amendmentsmentioning
confidence: 89%
“…Metagenomic analysis showed that Proteobacteria, Firmicutes, Actinobacteria and Bacteroidetes were the predominant phyla present in all the microcosms at day 300. The shared genera between manure-treated and control microcosm included Pseudomonas, Delftia, Methylobacterium, Dietzia, Bacillus, Propionibacterium, Bradyrhizobium, Streptomyces, Achromobacter, Microbacterium and Sphingomonas, some of which has been previously reported in oil-contaminated soils [41,43,45], with several members known for their ability to degrade aliphatic and aromatic hydrocarbons [51,52,53]. Whereas Pseudomonas and Sphingomonas have been previously associated with degradation of LMW PAHs [54,55], fermentative, CO 2 -assimilating and methanogenic microorganisms (Bacillus, Methylobacterium and Achromobacter) are known to be key players in HMW PAH degradation [55].…”
Section: Shift In Microbial Community With Manure Amendmentsmentioning
confidence: 89%
“…A third probable nod gene, HdN1_ nod , was found in the genome of Gammaproteobacterium strain HdN1 ( 5 , 9 11 ). Nitric oxide dismutation has been suggested in diverse catabolic functions including the oxidation of methane, long chain aliphatic hydrocarbons, benzene, and toluene ( 11 14 ). Our expanding understanding of nod diversity suggests there are more bacteria with nod capacity than the few identified through metagenomics or environmental studies ( 6 , 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…S1. In addition, the degradation of active aromatic hydrocarbons has been reported to be mutually coupled with the HNAD process (Zhu et al, 2020). While the above reports have revealed some influencing factors, the regulatory mechanism of cell growth and metabolism in the HNAD process remains unclear.…”
Section: Introductionmentioning
confidence: 99%